Tinjauan Literatur Kesenjangan Kredibilitas Merek: Penurunan Kepercayaan Merek Massal, Hipokrisi Korporat, dan Strategi Autentisitas Niche sebagai Respons Kompensasi Konsumen - Nurmoko, Aditya Hera; Heru Wahyudi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The global consumer market has undergone a significant transformation, creating an environment in which fragmented preferences and a widespread crisis of trust pose major challenges for brands. This systematic literature review examines the dynamics behind consumer migration from mass-market brands toward niche brands perceived as more authentic. The review focuses on five key constructs: Corporate Social Hypocrisy (CSH), Brand Trust (BT), Brand Hate, Brand Authenticity, and Consumer Need for Differentiation. The study proposes the Authenticity Trust Migration Model (ATM), a conceptual framework integrating both push and pull factors that shape consumer movement. CSH emerges as a destructive antecedent that erodes trust and triggers brand hate. As a compensatory response, consumers particularly those with high differentiation tendencies shift toward niche brands that offer symbolic authenticity and stronger value congruence. Niche authenticity is positioned not merely as a brand attribute but as an identity-signaling mechanism that helps consumers restore threatened self-concepts caused by the integrity failures of mass brands. These findings contribute theoretically to the understanding of differentiation as a moderating factor and offer strategic implications for brand management in an era of increasing public skepticism.